A Scoping Review of the Strategic Integration of Artificial Intelligence in Higher Education: Transforming University Excellence Themes and Strategic Planning in the Digital Era - Ammar Abulibdeh (15785928) (2025)
This scoping review discusses artificial intelligence's (AI) transformative role in strategic enhancement planning and academic excellence at Qatar University (QU). In response to the unprecedented rise in the integration of AI into higher education institutions worldwide, this study aims to understand its influence on institutional strategies and the development of student competencies. A literature search using Web of Science, Scopus, Google Scholar and IEEE Xplore. In this respect, 156 relevant studies were identified. Data extraction and charting for Covidence provided insights into the effects of AI on teaching, administrative efficiency and student learning experiences. The review emphasises how AI could enhance administrative efficiency and provide personalised learning. Still, it also points to challenges that must be faced: data privacy and reduced human interaction. The findings suggest that AI offers significant advantages in higher education but needs prudent implementation to meet the risks associated with adopting emerging technology. This would address the need for its effective complementarity to traditional educational methods. Other Information Published in: European Journal of Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/ejed.12908